Toward a New Generation of Fire‐Safe Energy Storage Devices: Recent Progress on Fire‐Retardant Materials and Strategies for Energy Storage Devices. Issue 3 (4th February 2022) - Yusuf, Abdulmalik; Li, Zhi; Yuan, Xiaoya; Wang, De‐Yi
Abstract: Over the last few decades, tremendous progress has been achieved in the development of advanced materials for energy storage devices. These achievements have largely enabled the adoption and transition to key technologies such as mobile phones, electric vehicles, and internet of things. However, the recent surge in fire accidents and explosions emanating from energy storage devices have been closely associated with the highly flammable components that make up these devices which have often led to the loss of life and property. Therefore, replacing flammable materials with fire retardant materials has been recognized as the critical solution to the ever‐growing fire problem in these devices. This review summarizes the progress achieved so far in the field of fire retardant materials for energy storage devices. Finally, a perspective on the current state of the art is provided, and a future outlook for these fire‐retardant materials, strategies, and new characterization methods is discussed. Abstract : Fire incidents emanating from electric devices are frequent, especially based on lithium‐ion batteries which are employed as the powerhouses of such devices. This review provides a comprehensive and critical summary of the progress achieved so far, as well as future directions and perspectives on the design of fire‐safe energy storage materials.